Pengaruh Minat Dan Keaktifan Mengikuti EkstrakurikulerPramuka Terhadap Kedisiplinan Siswa Kelas VSdn I Sudimoro Teras BoyolaliTahun Ajaran 2015/2016 - SUSANTI, DESI, Dra. Hj. Sri Hartini, SH., M.Pd (2016)
ABSTRACT EFFECT OF INTEREST AND LIVELINESS FOLLOW EXTRACURRICULAR SCOUT TO DISCIPLINE CLASS V SDN I SUDIMORO TERAS BOYOLALI By: Desi Susanti, A510120025, Department of Primary School Teacher Education, the Faculty of Education, University of Muhammadiyah Surakarta, 2015 This study aims to determine: (1) the effect of an interest in participating in extracurricular scouts to discipline students of class V SDN I Sudimoro Teras Boyolali. (2) the effect of liveliness in the following extracurricular scouts to discipline students of class V SDN I Sudimoro Teras Boyolali. (3) the effect of interest and activity in extracurricular memgikuti scouts to discipline students of class V SDN I Sudimoro Teras Boyolali. This type of research is quantitative research. Subjects in this study are students of class V SDN I Sudimoro Teras Boyolali. Data collection techniques used were questionnaires, interviews and documentation. Mechanical testing instruments used are validity and reliability testing. Techniques used prerequisite test is the test of normality and linearity test. Data analysis technique used was t test and f. The first hypothesis of the calculation results obtained t> t table (2.660> 2.042) and ρ-value <0.05 (0.012 <0.05). From the calculation of the second hypothesis is obtained t> t table (2.521> 2.042) and ρ-value <0.05 (0.017 <0.05). The third hypothesis of the calculation results obtained F count> F table (7.983> 3.32) and ρ-value <0.05 (0.002 <0.05). From the calculation results obtained regression coefficient interests amounted to 0.458 greater than the value of the regression coefficient of 0.334 liveliness. So that the conclusions of this study are (1) an interest in participating in extracurricular scout affect the discipline of students of class V SDN I Sudimoro Teras Boyolali. (2) to be active in extracurricular scouts follow affect the discipline of students of class V SDN I Sudimoro Teras Boyolali. (3) interest and active in extracurricular memgikuti scout affect the discipline of students in grade V SDN I Sudimoro Teras Boyolali Keywords: interest, liveliness and discipline